2009
DOI: 10.1002/col.20541
|View full text |Cite
|
Sign up to set email alerts
|

Deducing ink thickness variations by a spectral prediction model

Abstract: Most existing techniques for regulating the ink flow in offset presses rely on density measurements carried out on specially printed patches. In the present contribution, we develop a methodology to deduce ink thickness variations from spectral measurements of multichromatic halftone patches located within the printed page. For this purpose, we extend the Clapper-Yule spectral reflectance prediction model by expressing the transmittance of the colorants composed of superposed inks as a function of the ink tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The Yule-Nielsen model, the Clapper-Yule model and the Low scattering Clapper-Yule model are less accurate but need less measured samples for their calibration. Different criteria determine the optimal model for a given application: the number of calibration samples that can be printed, the types of halftones used in the reproduction process, the necessity of considering the transmittance of the inks [23] and the ease of using the model in inverse mode. If illumination and viewing conditions vary, the Clapper-Yule and low scattering Clapper-Yule models should be preferred since they incorporate explicitly the illumination and observation geometry.…”
Section: Discussionmentioning
confidence: 99%
“…The Yule-Nielsen model, the Clapper-Yule model and the Low scattering Clapper-Yule model are less accurate but need less measured samples for their calibration. Different criteria determine the optimal model for a given application: the number of calibration samples that can be printed, the types of halftones used in the reproduction process, the necessity of considering the transmittance of the inks [23] and the ease of using the model in inverse mode. If illumination and viewing conditions vary, the Clapper-Yule and low scattering Clapper-Yule models should be preferred since they incorporate explicitly the illumination and observation geometry.…”
Section: Discussionmentioning
confidence: 99%
“…(12) to multiple inks is not appropriate. Hersch et al have shown that the relative thickness of a printed solid ink layer depends on the presence of other superposed inks [18]. Beer's law enables expressing these ink thickness variations.…”
Section: Ink Superposition Reflectance Constraintsmentioning
confidence: 99%
“…This is possible because the ink spreading curves are calibrated in the first calibration step performed in Eq. (18). Moreover, a weight  i = 1 indicates that within the measured reflectances of the calibration set, there is also the measured colorant reflectance R i .…”
Section: Surface Coverage Based Colorant Reflectance Constraintsmentioning
confidence: 99%
See 2 more Smart Citations